The Effect of Hospital Environment on Patient Engagement and Perceived Experience: A Case Study Approach - Fatima Al-Kaabi (International Journal of Social Sciences: Current and Future Research Trends, 2025)
Patient engagement is a core dimension of quality healthcare; however, limited research has examined how hospital environments shape both engagement and patients’ perceived experiences. This study examines the impact of environmental factors on patient engagement across various hospital settings, with a focus on the physical environment’s influence on comfort, communication, and participation in care. A qualitative case study design was employed across five hospitals, varying in size and teaching status. Fifteen semi-structured interviews were conducted with patients, family members, and clinicians. Observational data and structured environmental assessments were also collected. Data were analysed thematically, with findings triangulated across data sources to enhance validity and reliability. The study developed five core themes from interview responses, including environmental comfort, communication with staff, involvement in care, emotional response to the environment, and suggestions for improvement. Hospitals with better environmental design (e.g., private spaces, calming aesthetics, and noise control) demonstrated stronger patient engagement practices. In contrast, institutions lacking spatial privacy and infrastructure for feedback reported limited engagement. Triangulated data highlighted that environmental design reinforced staff-patient interaction, family involvement, and the perceived inclusivity of care. Teaching hospitals and those with more than 100 beds more consistently demonstrate patient-enabling environments. Hospital environments significantly shape patient engagement and perceived experience. Comfort, dignity, and the ability to participate in care are influenced by physical design, spatial access, and organisational culture. Embedding patient engagement into hospital infrastructure and daily practices is essential for advancing patient-centred care. Patients and family members shared irrelevant details of how hospital settings impacted their participation, communication, and overall care experience.